The psychological impact of solitary: a longitudinal comparison of general population and long-term administratively segregated male inmates - Chadick, Carly D. (Legal and criminological psychology, 2018)
Purpose. This study expands upon existing research on the psychological impact of administrative segregation on inmates by addressing several methodological limitations in this body of literature. Methods. Using a pre–post design, this study compared male general population (GP) inmates in the United States to those with up to 4 years in segregated placement across scores on the MCMI-III. Results. While segregated inmates reported higher levels of distress (particularly on measures of anxiety, depressed mood, post-traumatic stress, and somatic complaints) compared to the GP at post-assessment, scores did not reach the clinical cut-off. Further, inmates generally did not deteriorate as time in restrictive housing increased. Conclusions. Thus, compared to the GP, who showed some improvement in functioning, segregated inmates remained largely the same. Rather than causing significant psychological damage, it is more likely that segregation is a barrier to opportunities for continued growth. Study limitations and recommendations for reforms in the use of segregation are presented.